2014
DOI: 10.3171/2014.5.spine121045
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following attempted en bloc resection of cervical chordomas in the C-1 and C-2 region versus the subaxial region: a multiinstitutional experience

Abstract: Object Chordomas involving the mobile spine are ideally managed via en bloc resection with reconstruction to optimize local control and possibly offer cure. In the cervical spine, local anatomy poses unique challenges, limiting the feasibility of aggressive resection. The authors present a multi-institutional series of 16 cases of cervical chordomas removed en bloc. Particular attention was paid to clinical outcome, complications, and recurrence. In addition, outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 36 publications
(42 reference statements)
1
46
0
1
Order By: Relevance
“…Dysphagia, dysphonia, pharyngeal erosion and permanent tracheostomy are described [33,[35][36][37][38]. Tumour location in the upper cervical spine was associated with increased complications compared to the subaxial spine in a retrospective review [35]. Wei et al [39] reported that 42.1 and 73.68 % of their patients experienced intraoperative and postoperative complications after intralesional spondylectomy of the upper cervical spine.…”
Section: Morbidity Of En Bloc Resectionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dysphagia, dysphonia, pharyngeal erosion and permanent tracheostomy are described [33,[35][36][37][38]. Tumour location in the upper cervical spine was associated with increased complications compared to the subaxial spine in a retrospective review [35]. Wei et al [39] reported that 42.1 and 73.68 % of their patients experienced intraoperative and postoperative complications after intralesional spondylectomy of the upper cervical spine.…”
Section: Morbidity Of En Bloc Resectionmentioning
confidence: 97%
“…Vertebral artery sacrifice can result in significant morbidity in the absence of collateral flow. Dysphagia, dysphonia, pharyngeal erosion and permanent tracheostomy are described [33,[35][36][37][38]. Tumour location in the upper cervical spine was associated with increased complications compared to the subaxial spine in a retrospective review [35].…”
Section: Morbidity Of En Bloc Resectionmentioning
confidence: 99%
“…33 Molina et al presented a multiinstitutional case series in which en bloc resection of cervical chordomas was attempted. 40 Upper cervical spine (C-1 and C-2) chordomas were associated with a dramatically higher rate of complications compared with subaxial chordomas (71% vs 22%, respectively) and higher rates of recurrence. Given the complex vascular, osseoligamentous, and important neuroanatomy that presents unique surgical challenges in cases of atlantoaxial chordomas, and given the significantly higher rate of complications, the authors advocated intralesional resection for C-1 and C-2 chordomas rather than en bloc resection.…”
Section: Discussionmentioning
confidence: 98%
“…C1-2 chordomas have been reported to have a 71% risk of complications. 40 The authors of a series reviewing the complications of 220 en bloc spinal operations reported that 33% of their patients had major surgical complications, with those harboring primary malignant spinal tumors having a higher risk of complications. 8 One study with long-term follow-up after proton radiotherapy for chordoma noted a Grade 3-4 toxicity risk of 13%.…”
Section: Discussionmentioning
confidence: 99%
“…30 In a multiinstitutional study of 16 patients in whom C1-2 en bloc resections for chordoma were attempted, the likelihood of achieving the desired marginal margins was only 29% in contrast to a rate of 79% in a control population in which subaxial en bloc resections were attempted. Although the survival rate was not significantly different between the groups, there was a significantly higher rate of local and distant recurrence in the patients who underwent high cervical resections.…”
Section: Discussionmentioning
confidence: 99%